A visual based cognitive assessment tool (VCAT) for diagnosis of dementia in a multilingual Asian population / Sarah Iyang Kiyu - Sarah , Iyang Kiyu (2017)
Background Mild cognitive impairment (MCI) can be regarded as a risk for developing dementia. Early diagnosis of MCI enables timely medical and non-medical intervention for patients as well as social support networks for caregivers. This is essential as the prevalence of dementia is increasing worldwide.